Calcium is the molecular switch shifting the phytosulfokine receptor 1 (PSKR1) from kinase to guanylate cyclase activity - Muleya, Victor; Wheeler, J. I.; Freihat, L.; Thomas, L.; Marondedze, C.; Manallack, D. T.; Ruzvidzo, O.; Kwezi, L.; Gehring, C.; Irving, H. R. (International Conference on Arabidopsis Research (ICAR), 2016)
Conference presentation